Interpretação deôntica e difusa das normas jurídicas - Ferreira, Rodrigo Costa (2014)
The contemporary deontic logic uses besides of the deontic operators obligatory, permitted e forbidden also modern symbolic and mathematical techniques in the analysis of normative discourses. In that sense, given the complexity of this type of discourse, even today, a series of s questions are raised, as follows here: (i) What is the meaning of the expression “to be obligatory”? (ii) What is obligatory is the case?, (iii) What is the case, is permitted?, (iv) Can we consider deontic logic as a mere extension of modal logic, i.e. is it possible to convert all modal axioms into deontic axioms (equally valid)?, (v) The “possible worlds semantics” proposed by Kripke allows us to interpret adequately, or even intuitively, deontic propositions?, (vi) The algebraic semantics of closures developed by McKinsey and Tarski Jónsson to interpret the modal system S4 enables correctly to interpret the deontic propositions?, (vii) Observing the necessity of to understand the obligation operator according to the idea of degrees of truth, it would be more correct interpret this deontic operator with semantic structures of the fuzzy logic? We intend throughout this thesis to present answers to each of these questions. As initial strategy, we show that the notion of obligatory can be better understood in terms of the idea of gradation. We investigate this in the context of morality, politics, legality and logic (Chapter 01 and Chapter 02). The fuzzy logic is able to formalize vague expressions such as “more or less true”. This kind of logic admits to the truth different degrees. Based on this, we propose a fuzzy semantic able to interpret more adequately the obligation deontic operator, which binds of form “more or less strong” an agent to perform the obligatory legal norm (Chapter 03). This approach proves itslef to be quite signiﬁcant once it allows to (i) validate of axioms of the deontic formal system OS5, (ii) invalidate the formulas not intuitive, and (iii) eliminate the following deontic paradoxes: “Paradox of Derived Obligation”, “Paradox of Compromise” (Prior’s Paradox), “Paradox of the Minor Murderer” and “The Must versus Ought Dilemma” (Chapter 4).